Barium titanate-enhanced hexagonal boron nitride inks for printable high-performance dielectrics. (21st May 2022) - Kim, Hyunho; Arbab, Adrees; Fenech-Salerno, Benji; Yao, Chengning; Macpherson, Ryan; Kim, Jong Min; Torrisi, Felice
Abstract: Printed electronics have been attracting significant interest for their potential to enable flexible and wearable electronic applications. Together with printable semiconductors, solution-processed dielectric inks are key in enabling low-power and high-performance printed electronics. In the quest for suitable dielectrics inks, two-dimensional materials such as hexagonal boron nitride (h-BN) have emerged in the form of printable dielectrics. In this work, we report barium titanate (BaTiO3 ) nanoparticles as an effective additive for inkjet-printable h-BN inks. The resulting inkjet printed BaTiO3 /h-BN thin films reach a dielectric constant ( ε r ) of ∼16 by adding 10% of BaTiO3 nanoparticles (in their volume fraction to the exfoliated h-BN flakes) in water-based inks. This result enabled all-inkjet printed flexible capacitors with C  ∼ 10.39 nF cm −2, paving the way to future low power, printed and flexible electronics.